The revival of 1857-58 : interpreting an American religious awakening - Long, Kathryn, 1950- (Religion in America series (Oxford University Press), 1998)
This book provides a fresh, in-depth examination of the Revival of 1857-58, a widespread religious awakening most famous for urban prayer meetings in major metropolitan centers across the United States. Often mentioned in religious history texts and articles but overshadowed by scholarly attention to the first and second "Great Awakenings," the revival has lacked a critical, book-length analysis. This study will help to fill this gap and to place the event within the context of Protestant revival traditions in America. The book combines insights from contemporary scholarship concerning revivals, women's history, and nineteenth-century mass print with extensive primary source research.